2007
DOI: 10.1002/app.25796
|View full text |Cite
|
Sign up to set email alerts
|

Modification of isotactic polypropylene by the free‐radical grafting of 1,1,1‐trimethylolpropane trimethacrylate

Abstract: The chemical modification of isotactic polypropylene was performed by the free-radical-promoted grafting of 1,1,1-trimethylolpropane trimethacrylate (TMPTMA) in the presence of dicumyl peroxide (DCP) as the initiator. The reaction was carried out both in a batch internal mixer and in a corotating twin-screw extruder; the effects of the peroxide and monomer concentrations on the extent of modification in terms of the grafting efficiency and polymer chain structure variations were investigated. The modified samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…These include an increase in the crystallization temperature and crystallization rates. 810 We have recently attributed this phenomenon to the formation of coagent-rich cross-linked nanoparticles that form within these systems and act as nucleating sites for crystallization and foaming. 11…”
Section: Introductionmentioning
confidence: 99%
“…These include an increase in the crystallization temperature and crystallization rates. 810 We have recently attributed this phenomenon to the formation of coagent-rich cross-linked nanoparticles that form within these systems and act as nucleating sites for crystallization and foaming. 11…”
Section: Introductionmentioning
confidence: 99%
“…T m of the PP‐modified has declined from the pure PP beads. This may be due to the grafted TMI short chains that form a disordered branched structure, which destroyed the uniform molecular structure of PP chains . The degradation of the polymer chains during PP modification was also one of the reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the TG spectrum in Figure and the data in Table showed that T d5 and T d10 of PP‐g‐TMI decreased significantly compared with the pure PP beads; after cyclotrimerization was completed, the decomposition temperatures likely increased. In the first stage, T m and T d decreased because the regular structure of the PP chains was disrupted; the PP chains were disrupted because the grafted TMI is a short chain forming a randomly branched structure . The networked structure consisted of heterocyclic rings formed through cyclotrimerization.…”
Section: Resultsmentioning
confidence: 99%
“…In the first stage, T m and T d decreased because the regular structure of the PP chains was disrupted; the PP chains were disrupted because the grafted TMI is a short chain forming a randomly branched structure. 30 The networked structure consisted of heterocyclic rings formed through cyclotrimerization. These rings were rigid structures limiting the motion of chains.…”
Section: Resultsmentioning
confidence: 99%